Impact of Different Clinical Perfusates During Normothermic Ex Situ Liver Perfusion on Pig Liver Transplant Outcomes in a DCD Model. Issue 4 (April 2019) - Linares-Cervantes, Ivan; Kollmann, Dagmar; Goto, Toru; Echeverri, Juan; Kaths, Johan Moritz; Hamar, Matyas; Urbanellis, Peter; Mazilescu, Laura; Rosales, Roizar; Bruguera, Claudia; Oquendo, Fabiola; Ganesh, Sujani; et al.
Abstract : Background: Human albumin/dextran (HA-D), bovine-gelatin (BG), and packed red blood cells plus plasma have been used in European and North-American clinical trials of normothermic ex situ liver perfusion (NEsLP). We compared the effects of these perfusates in a porcine model during NEsLP and after transplantation. Methods: Porcine livers were retrieved 30 minutes after circulatory death. After 5 hours of NEsLP, grafts were transplanted. Three groups (n = 6) were assessed (HA-D vs BG vs whole blood [WB]). One group of static cold storage (SCS) was evaluated for comparison with the perfusion groups. Hemodynamic variables, liver and endothelial injury, and function were assessed during NEsLP and posttransplantation. Results: Hepatic artery flow was higher since the beginning of NEsLP in the HA-D group (HA-D, 238 ± 90 mL/min vs BG, 97 ± 33 mL/min vs WB, 148 ± 49 mL/min; P = 0.01). Hyaluronic acid was lower in the HA-D at the end of perfusion (HA-D, 16.28 ± 7.59 ng/μL vs BG, 76.05 ± 15.30 ng/μL vs WB, 114 ± 46 ng/μL; P < 0.001). After transplant, aspartate aminotransferase was decreased in the HA-D group when compared with the rest of the groups (HA-D, 444 ± 226 IU/L vs BG, 1033 ± 694 IU/L vs WB, 616 ± 444 IU/L vs SCS, 2235 ± 1878 IU/L). At 5 hours after transplant, lactate was lower in the HA-D group (HA-D, 3.88 ± 1.49 mmol/L vs BG, 7.79 ± 2.68 mmol/L vs WB, 8.16 ± 3.86 mmol/L vs SCS, 9.06 ± 3.54 mmol/L; P = 0.04). International Normalized Ratio was improved in HA-D group compared to the rest of the groups (HA-D, 1.23 ± 0.30 vs BG, 1.63 ± 0.20 vs WB, 1.50 ± 0.31 vs SCS, 1.97 ± 1.55; P = 0.03) after transplantation. In contrast, BG displayed lower aspartate aminotransferase levels during NEsLP (HA-D, 183 ± 53 IU/L vs BG, 142 ± 52 IU/L vs WB, 285 ± 74 IU/L; P = 0.01) and less cleaved-caspase-3 staining (HA-D, 2.05 ± 0.73% vs BG, 0.95 ± 1.14% vs WB, 1.74 ± 0.54% vs SCS, 7.95 ± 2.38%) compared with the other groups. On the other hand, the bile from the WB showed higher pH (HA-D, 7.54 ± 0.11 vs BG, 7.34 ± 0.37 vs WB, 7.59 ± 0.18) and lower glucose levels (HA-D, 0.38 ± 0.75 mmol/L vs BG, 1.42 ± 1.75 mmol/L vs WB, 0 ± 0 mmol/L) by the end of perfusion. Conclusions: Overall HA-D displayed more physiologic conditions during NEsLP that were reflected in less graft injury and improved liver function and survival after transplantation. Optimization of the perfusates based on the beneficial effects found with these different solutions would potentially improve further the outcomes through the use of NEsLP in marginal grafts. Abstract : Supplemental digital content is available in the text.